Novelties in Oxypetalum (Apocynaceae: Asclepiadoideae): a new species and revalidation of the name O. megapotamicum - Keller, Hector Alejandro (2021)
Based on a specimen collected in Santa Catarina state, Brazil, the new species Oxypetalum kassneri is described and illustrated. Moreover, a molecular phylogenetic analysis allows to propose the revalidation of O. megapotamicum, a species currently placed in the genus Ditassa. The neotype of D. megapotamica and the lectotype of D. oxypetala are designated here.